PENENTUAN LOKASI GUDANG DARURAT BENCANA DI PROVINSI DKI JAKARTA DENGAN PENDEKATAN AHP, CLUSTER ANALYSIS, DAN TOPSIS - Aries Susanty; Arfan Bakhtiar; Adhitya Sulistyawan (Universitas Mercu Buana, 2016)
Abstract: This study aims to determine the location of the disaster emergencywarehouse as a place for storing food and beverages as well as medicines for firstaid during a flood. Objects selected for this study is Jakarta. Flooding is aproblem that often occurs in Jakarta as a result of heavy rainfall and thegeographical conditions of Jakarta. Forty percent of the area of Jakarta is belowsea level and there are 13 rivers flowing through Jakarta and has estuary inJakarta Bay. This study uses three approaches, namely analytic hierarchy process(AHP), cluster analysis and technique for an order of preference by similarity toideal solution (TOPSIS). The results of data processing by using AHP showedthat criteria and sub-criteria with the highest weighting for selecting the locationof disaster emergency warehouse were owned by delivery time. Furthermore,the results of data processing using cluster analysis and TOPSIS indicated thatthere were five potential sites for disaster emergency warehouse in order ofpriority: Sub-district Makasar followed by Kebon Jeruk, Tanjung Priok, Senen,and Cilandak.